2004
DOI: 10.1182/blood-2003-04-1155
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic activation of Vα24+Vβ11+ NKT cells in human subjects results in highly coordinated secondary activation of acquired and innate immunity

Abstract: IntroductionHuman V␣24 ϩ V␤11 ϩ natural killer T (NKT) cells are a distinct CD1d-restricted lymphoid subset specifically activated and induced to proliferate by ␣-galactosylceramide (␣-GalCer) (KRN7000) presented by CD1d on antigen-presenting cells (APCs), including dendritic cells (DCs) and monocyte-derived DCs (MoDCs). [1][2][3][4][5] Preclinical murine in vivo and human in vitro data suggest NKT cell activation may be therapeutic for human malignancy. 6,7 NKT cells have direct antitumor cytotoxicity, depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
270
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(280 citation statements)
references
References 39 publications
6
270
4
Order By: Relevance
“…With the development of therapeutic approaches with the potential to activate NKT cells in vivo (Nieda et al, 2003) and expand NKT cells in vitro (Nieda et al, 1999;Nicol et al, 2000a;Takahashi et al, 2000), it is important to more clearly define their applicability in the clinical setting. Previous data indicate that NKT cells may be decreased in some cancer patients (Kawano et al, 1999a;Tahir et al, 2001;Motohashi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of therapeutic approaches with the potential to activate NKT cells in vivo (Nieda et al, 2003) and expand NKT cells in vitro (Nieda et al, 1999;Nicol et al, 2000a;Takahashi et al, 2000), it is important to more clearly define their applicability in the clinical setting. Previous data indicate that NKT cells may be decreased in some cancer patients (Kawano et al, 1999a;Tahir et al, 2001;Motohashi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, based on our previous study of postinfarct heart failure [17], αGC administration may attenuate also LV remodeling and reduce mortality after MI. To date, several clinical trials (Phase I/II) using activated iNKT cells by αGC have been conducted in patients with cancer [45][46][47][48][49]. No severe adverse events were observed in these trials.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…18 The results of a clinical study using IL-4 and GM-CSF-cultured DCs loaded with aGalCer suggested the feasibility of the procedure. 23,24 Thus, inducing the activation and expansion of endogenous Va24 1 NKT cells by aGalCer-loaded DCs would be a promising strategy for cancer immunotherapy.…”
mentioning
confidence: 99%